2013
DOI: 10.1021/ie403009c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Study of the Valid Apparent Interface Thickness in Particulate Materials with Ellipsoidal Particles

Abstract: When interfacial layers are viewed as a separate phase, the interface thickness plays an essential role in assessing physicomechanical properties of particulate materials. However, the actual interface thickness is difficult to determine because of the opacity of particulate materials. The apparent interface thickness obtained from sectional analysis is often overestimated, due to the irregularity of surface texture of grain that gives rise to the normal of a cross-sectional plane nonperpendicular to the grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that various parameters of a sheared granular assembly depend systematically on the sphericity of the particles 12,59,60 (as a general measure of the deviation from the spherical shape). Our data in Fig.…”
Section: Temporal Evolutionmentioning
confidence: 99%
“…Previous studies suggested that various parameters of a sheared granular assembly depend systematically on the sphericity of the particles 12,59,60 (as a general measure of the deviation from the spherical shape). Our data in Fig.…”
Section: Temporal Evolutionmentioning
confidence: 99%
“…In addition, the influences of ellipsoidal particle size distribution, shape, and volume fraction of ellipsoidal aggregates on the configuration parameters are evaluated with stereological methods proposed by and the serial section analysis technique. An approximate analytical model for the volume fraction of soft interface layers is proposed by Xu et al (2014b) on the basis of a theory of the nearest-surface distribution functions and geometric characteristics of polydisperse ellipsoidal particle systems. A theoretical model that adopts a threephase composite ellipsoid structure of a generalized selfconsistent scheme is presented to further predict the effective transport properties of particulate composites containing such soft interface layers.…”
Section: Introductionmentioning
confidence: 99%